The Application of the Cardiff Count-to-Ten Method for Fetal Well-Being Assessment in Oligohydramnios: A Case Report - Eny Dewi Pamungkas; Agustin Dwi Rachma Nisa; Delli Nurilah Sari; Ranum Muntazia; Erna Puspita Sari (NERS Jurnal Keperawatan, 2025)
Introduction: The severity of amniotic fluid reduction can affect fetal movement. To determine the well-being of the fetus, fetal movement can be counted daily. Methods: This study is a case report involving one case with the aim of determining fetal movement in a pregnant woman G2P1A0 with oligohydramnios. Data was collected through patient medical records and observation of adherence to filling out fetal movement stickers. Results: The results showed that the average fetal movement count ranged from 22 to 29 per day. This number is normal because the value of fetal movement is more than 10 times in a duration of 12 hours. It can be concluded that there was no decrease in fetal movement during the patient pregnancy period. Fetal movement monitoring is a subjective method performed by the mother. This becomes inaccurate because mothers who are too busy and do not concentrate on recording can report errors in fetal movement. Discussion/Conclusion: Fetal movement counting also needs to be followed by other examinations such as cardiotocography and biophysical profile to be able to accurately assess fetal well-being, especially in pregnant women at risk.